Men in Place : Trans Masculinity, Race, and Sexuality in America - Abelson, Miriam J. (Book collections on Project MUSE., 2019)
"Daring new theories of masculinity, built from a large and geographically diverse interview study of transgender men American masculinity is being critiqued, questioned, and reinterpreted for a new era. In Men in Place Miriam J. Abelson makes an original contribution to this conversation through in-depth interviews with trans men in the U.S. West, Southeast, and Midwest, showing how the places and spaces men inhabit are fundamental to their experiences of race, sexuality, and gender. Men in Place explores the shifting meanings of being a man across cities and in rural areas. Here Abelson develops the insight that individual men do not have one way to be masculine--rather, their ways of being men shift between different spaces and places. She reveals a widespread version of masculinity that might be summed up as "strong when I need to be, soft when I need to be," using the experiences of trans men to highlight the fundamental construction of manhood for all men. With an eye to how societal institutions promote homophobia, transphobia, and racism, Men in Place argues that race and sexuality fundamentally shape safety for men, particularly in rural spaces, and helps us to better understand the ways that gender is created and enforced."--EBSCO.